Uses of plants, animal and mineral substances in Mediterranean ethno-veterinary practices for the care of small ruminants. (20th June 2015) - Piluzza, G.; Virdis, S.; Serralutzu, F.; Bullitta, S.
Abstract: Ethno-pharmacological relevance: The cultural heritage of Sardinian shepherds is rapidly vanishing and survives in the memory of elderly people. The objective of our study was not only to report the usage of plants and their preparation for administration but also the use of other remedies of different origin arising from traditional ethno-veterinary knowledge, as Sardinian shepherds were used to employ plants, animals, minerals and combinations of several substances to prepare remedies for prophylaxis or therapy on their animals. Materials and methods: The work was carried out in rural areas of the island of Sardinia (Italy) by interviewing shepherds and filling questionnaires in order to record ethno-veterinary practices traditionally used for animal health care. Results: Ethno-veterinary remedies traditionally utilised for treatments of small ruminants against ecto-and endo-parasites, gastrointestinal diseases, viral and bacterial diseases, wounds, sprains and bruises were identified. Non herbal remedies outnumbered the herbal ones, as usually plant species were mainly used for the care of cattle and equines. A total of 150 ethno-veterinary uses were documented for the treatment of 33 animal conditions, a detailed account of the formulations and their administration to sheep and goats was provided. Herbal remedies involved the use of twenty two spontaneous species and seven cultivated species. Conclusions: This study identifies remedies used in ethno-veterinary practices for small ruminants care in Sardinia, the second major Mediterranean island which has agro-pastoral activities dating back to Neolithic. Moreover, the danger of losing oral traditions, and the increasing attention towards traditional remedies as potential sources of natural products for improving animal health and welfare, support the interest of our survey. Graphical abstract: